Antioxidant Activity in Salt‐Stressed Barley Leaves: Evaluating Time‐ and Age‐Dependence and Suitability for the Use as a Biochemical Marker in Breeding Programs. Issue 4 (29th April 2014) - Fan, Y.; Zhu, M.; Shabala, S.; Li, C. D.; Johnson, P.; Zhou, M. X.
Abstract Soil salinity disturbs the equilibrium between reactive oxygen species (ROS) production and removal, leading to a dramatic increase in ROS concentration and oxidative damage. Enzymatic scavenging is one of the two main mechanisms involved in ROS detoxification in plants. This study has investigated the role of major antioxidant (AO) enzymes in mitigating salinity‐induced oxidative stress in plant shoots. Firstly, two barley varieties were used to evaluate the activity of major AO enzymes in different leaves and at different times after salt treatment. Our results showed that AO enzyme activities had strong tissue and time specificity. A further study was conducted using six barley varieties contrasting in salinity tolerance. AO enzyme activities and proline contents were measured in the third leaves of seedlings after plants were treated with 240 mm NaCl for 10 days. No significant correlation was revealed between leaf AO activity and either plant grain yield or plant survival rate under salt stress. In contrast, a significant increase in leaf proline content under salt stress was found in all sensitive varieties, while in most tolerant varieties, salt stress did not change leaf proline level. It is concluded that although salinity induces changes in leaf AO enzyme activities, the changes cannot be used as biochemical indicators in breeding for salinity tolerance.